New Graduate Nurses' Transition in Critical Care: A Systematic Review of Qualitative Evidence - Stevenson, Lana (Université d'Ottawa / University of Ottawa, 2023)
Background: The nursing shortage has been heightened by the COVID-19 pandemic. To mitigate shortages, we must rely on a steady influx of new graduate nurses. A considerable preparation-practice gap is affecting transition to practice. The transition experience to critical care is further amplified, as these environments involve specialized training and knowledge. Objective: To describe the transition of new graduate nurses into critical care nursing practice Design: Qualitative evidence synthesis Setting(s): Critical care settings: intensive care units and emergency departments. Participants: New graduate nurses with at least 2 years’ experience beginning their career in critical care Methods: We searched Ovid MEDLINE® ALL, including EPub, Ahead of Print and In-Process; Other Non-Indexed Citations, Embase Classic + Embase, PsycINFO, CINAHL and Education Source on EBSCO and the Nursing and Allied Health and ERIC databases on ProQuest. Results: Twelve studies met inclusion criteria. Seventy-eight findings were extracted and grouped into six synthesized themes: (i) Barriers and Facilitators to Communication in Critical Care; (ii) Struggling with Uncertainty during Difficult Situations; (iii) Support and Its Impact on Acceptance and Attaining Desirable Nursing Qualities in Critical Care; (iv) Knowledge Develops with Time and Exposure to Complex Clinical Situations; (v) Being a Student in Critical Care; and (vi) Novel Perspectives Related to COVID-19. Conclusions: This qualitative evidence synthesis affirms that NGN transition is a complex phenomenon in critical care. Offering support, guidance and ensuring access to resources during transition to professional practice could improve new graduate nurse retention, as well as improving confidence and competence in the workplace.
Keywords: new graduate nurse; transition; critical care; transition shock; systematic review